The “New Transamazonian Highway”: BR-319 and Its Current Environmental Degradation - Lima, Mendelson; Santana, Dthenifer Cordeiro [UNESP]; Maciel Junior, Ismael Cavalcante; da Costa, Patricia Monique Crivelari; de Oliveira, Pedro Paulo Gomes; de Azevedo, Raul Pio; Silva, Rogerio de Souza; Marinho, Ubiranei de Freitas; da Silva, Valdinete; de Souza, Juliana Aparecida Arantes; Rossi, Fernando Saragosa [UNESP]; Delgado, Rafael Coll; et al. (MDPI, 2022)
The Brazilian government intends to complete the paving of the BR-319 highway, which connects Porto Velho in the deforestation arc region with Manaus in the middle of the Amazon Forest. This paving is being planned despite environmental legislation, and there is concern that its effectiveness will cause additional deforestation, threatening large portions of forest, conservation units (CUs), and indigenous lands (ILs) in the surrounding areas. In this study, we evaluated environmental degradation along the BR-319 highway from 2008 to 2020 and verified whether highway maintenance has contributed to deforestation. For this purpose, we created a 20 km buffer adjacent to the BR-319 highway and evaluated variables extracted from remote sensing information between 2008 and 2020. Fire foci, burned areas, and rainfall data were used to calculate a drought index using statistical tests for a time series. Furthermore, these were related to data on deforestation, CUs, and ILs using principal component analysis and Pearson’s correlation. Our results showed that 743 km2 of forest was deforested during the period evaluated, most of which occurred in the last four years. A total of 16,472 fire foci were identified. Both deforestation and fire foci occurred mainly outside the CUs and ILs. The most affected areas were close to capital cities, and after resuming road maintenance in 2015, deforestation increased outside the capital cities. Current government policy for Amazon occupation promotes deforestation and will compromise Brazil’s climate goals of reducing greenhouse gas (GHG) emissions and deforestation.
Keywords: Amazon; Deforestation; Environment; Fire; Remote sensing analysis